2020
DOI: 10.1002/hbm.25312
|View full text |Cite
|
Sign up to set email alerts
|

Unique deficit in embodied simulation in autism: An fMRI study comparing autism and developmental coordination disorder

Abstract: A deficit in pre‐cognitively mirroring other people's actions and experiences may be related to the social impairments observed in autism spectrum disorder (ASD). However, it is unclear whether such embodied simulation deficits are unique to ASD or instead are related to motor impairment, which is commonly comorbid with ASD. Here we aim to disentangle how, neurologically, motor impairments contribute to simulation deficits and identify unique neural signatures of ASD. We compare children with ASD (N = 30) to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 69 publications
3
14
0
1
Order By: Relevance
“…Reduced BOLD activity has also been reported in both the left (Licari et al, 2015;Zwicker et al 2010) and right IFG (Debrabant et al, 2013;Kilroy et al, 2020;Reynolds et al, 2015b) in children with DCD. Bilaterally, the IFG is involved during MI, AO and action execution (Hardwick et al, 2018).…”
Section: Aomi In Children Withmentioning
confidence: 72%
See 3 more Smart Citations
“…Reduced BOLD activity has also been reported in both the left (Licari et al, 2015;Zwicker et al 2010) and right IFG (Debrabant et al, 2013;Kilroy et al, 2020;Reynolds et al, 2015b) in children with DCD. Bilaterally, the IFG is involved during MI, AO and action execution (Hardwick et al, 2018).…”
Section: Aomi In Children Withmentioning
confidence: 72%
“…Furthermore, this would align with the recent call by Brown-Lum & Zwicker (2017) for mental training interventions to target supressed brain regions in children with DCD. Two AON regions reported to be impaired in this population are the precentral gyrus and pars opercularis of the IFG (Kilroy et al, 2020;Reynolds et al, 2015b). While the evidence for the suppression of these motor regions has only been obtained through AO and imitation in DCD (Reynolds et al, 2015b;2015a), these regions also play a role in MI and action execution in adults (Hardwick et al, 2018) and children (Reynolds et al, 2015b).…”
Section: Aomi In Children Withmentioning
confidence: 82%
See 2 more Smart Citations
“…A total of 136 right-handed individuals aged 8–17 in either DCD ( N = 27; mean age = 11.75, SD = 2.31), ASD ( N = 57; mean age = 11.89, SD = 2.29), or TD ( N = 53; mean age = 11.75, SD = 2.13) groups completed the study. This study was part of a larger study that included brain imaging components, thus some inclusion criteria were based on those requirements [ 88 ]. Using the effect sizes from a meta-analysis on TD and ASD by Ben Sasson et al [ 89 ], we conducted a power analysis and found that the sample sizes we had were sufficient to achieve 97.5% power.…”
Section: Methodsmentioning
confidence: 99%